Cytomegalovirus Congenital Cataract - Wahyutomo, Ridha (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Cytomegalovirus congenital infection is an infection caused by the the subfamily Ã¢ Herpesviridae, during pregnancy. The incidence of infections among newborn infants is 1 %. One of the effects of congenitally acquired infection is the congenital cataract. A 6-year-old child complained to have a blurred vision diagnosed with cytomegalovirus congenital cataract. The diagnosis was confirmed by a positive serology testing for Ig M and Ig G CMV. The laboratory test using Giemsa staining to find inclusion bodies and a faster PCR could not be carried out (Sains Medika, 3(1):84-88).